The Role of Traffic Technology Students Statements in Sociological Studies of Social Exploitation - Ostan, Iztok (Promet - Traffic&Transportation, 2004)
The empirical sociological studies of exploitation are nowadaysrare in Slovenia and in other countries as well. Researchamong Slovene students showed that according to their statementsthere is much exploitation in Slovenia and that it hasbeen increasing. It showed also that statements of students donot differ much from the results of public opinion research regardingexploitation, nor from the statements of irregular studentswith long working experience. It was also found that thereare no substantial differences in statements of Italian and Slovenestudents. Traffic technology students are a group amongfull-time students who agree most with the statements that thereis much exploitation and that it has been increasing. A hypothesiswas set that statements of these students could be used as anindicator of general student opinion regarding exploitation.